Telaah Korelatif Antara Keharaman Riba dan Bunga Bank - Anwar Habibi Siregar (Yayasan Al-Ahliyah Al-Islamiyah Aek Badak, 2022)
The purpose of this research is to find out the legal differences between bank interest and usury. This study used a qualitative method with a library research style using content analysis techniques. The findings of this study indicate that there is an agreement among the scholars regarding the prohibition of usury and differences of opinion regarding the prohibition of bank interest. The scholars agree that the prohibition of usury is due to the addition of transactions (contracts). This has been explicitly confirmed by the texts (al-Qur'an and Sunnah). The scholars differed in terms of the illat (reason) for the prohibition of bank interest. They argue that what is forbidden is multiplied (unnatural) interest and found an element of unfair by anyone of the parties. While the interest is not multiplied and still in fair, then it's halal or legal.